Plastic rotation capacity of lightweight-aggregate concrete beams - Bernardo, Luís Filipe de Almeida (2018)
Submitted by Miguel Costa Santos Nepomuceno (mcsn@ubi.pt) on 2018-01-05T11:55:12Z No. of bitstreams: 1 40.LB,MN,HP- Plastic rotation capacity of LWA concrete beams, JCEM, Jan 2016 (ISI).pdf: 1375777 bytes, checksum: dc0fcade1061dbabeb9871e1885af262 (MD5)